Determinan Dana Pihak Ketiga Bank Umum Syariah Di Indonesia - Dadang Husen Sobana; Ricky Hamzah; Sri Habibah (LPPM ISNJ Bengkalis, 2021)
Third-party funds at Islamic commercial banks in Indonesia fluctuated. The factors that determine the accumulation of third-party funds are essential for Islamic banks' financial stability and management. This study aims to show and describe the effect of gross domestic product and inflation on third-party funds partially and simultaneously. The research method used is descriptive-associative with a quantitative approach. The population used is Islamic commercial banks in Indonesia. Data analysis using multiple linear regression. The results show that gross domestic product and inflation partially affect third-party funds in Islamic commercial banks in Indonesia. Meanwhile, simultaneously gross domestic product and inflation have a significant effect with a contribution of 85.5% to third-party funds in Islamic commercial banks in Indonesia. The increase in third-party funds depends on Indonesia's macroeconomic conditions, the dominant macroeconomic influencing the collection of third-party funds in Islamic commercial banks in Indonesia.